Awareness Of Thalassemia In Male And Female Students - Qayyum, Rimsha; Zulfiqar, Taiba; Ali , Abid (Medical Science Journal for Advance Research, 2022)
Objective:-Objective of this look at is to access the awareness stage of Thalassaemia in University college students. Method: Study design was chosen to be crosssectional prospective. Sample size for this study was taken as 64. . A wellstructured:data collecting form or questionnaire was created, analysedand filled out during the interview.The data was summarized using descriptive statistics. Results The total 64 cases of all age groups were enrolled in this study. The are 64 cases of all age group are involved in this study in which there are 21 male (32.8%) and 43 females (67.2%). In this survey out of 64 persons 53 persons know about thalassemia. 5 people know about thalassemia gene. 40 persons know that thalassemia is inherited from parents. 53 persons know that thalassemia is blood related disease. 45 persons know severe anaemia is the clinical presentation of thalassemia. 25 persons know about the permanent treatment of thalassemia. 37 persons know that thalassemia is treated by bone marrowtransplantation.However, the study findings revealed that education status had a substantial impact. Conclusion:- Females have more awareness about thalassemia then man.